The impact of surgical quality on prognosis in patients undergoing rectal carcinoma surgery after preoperative chemoradiation - Kiehlmann, Marcus; Weber, Klaus; Göhl, Jonas; Fietkau, Rainer; Agaimy, Abbas; Hohenberger, Werner; Merkel, Susanne (International Journal of Colorectal Disease, 2016)
The aim of the study was to analyse the impact of surgical quality on the prognosis of rectal carcinoma patients who underwent preoperative long-term chemoradiation and TME surgery.In a total of 314 patients, four quality indicators, including plane of surgery, pathological circumferential resection margin (pCRM), intraoperative local tumour cell dissemination and anastomotic leakage, were analysed with respect to locoregional recurrence, distant metastasis and overall survival.In 260 (82.8 %) of the patients, all four quality indicators were fulfilled. In 30 (9.6 %) of the patients, at least one quality indicator was not fulfilled; in 24 (7.6 %) of the patients, the data were not complete. Locoregional recurrence was significantly increased in patients who underwent surgery in the muscularis propria plane, who had a pCRM <= 1 mm or who experienced local tumour cell dissemination. In patients who had at least one quality indicator that was not fulfilled (suboptimal surgical quality), the 5-year rate of locoregional recurrence in those patients was 23.1 % compared to 4.8 % in patients who underwent optimal surgery (P = 0.001). In multivariate analysis, suboptimal surgery (hazard ratio (HR) 3.9; P = 0.020), abdominoperineal excision (HR 4.7; P = 0.003) and poor regression of primary tumours (HR 8.5; P < 0.001) were identified as independent prognostic factors for locoregional recurrence. In contrast to type of surgical treatment, ypT, ypN and regression grade, the quality of surgery did not significantly influence distant metastasis or overall survival.Even after preoperative chemoradiation, the surgical quality still has a strong impact on local control in patients with rectal carcinoma.
EVALuna2:6711